Identification of bacteria isolated from malt, with the emphasis on lactic acid bacteria and their influence on brewer's yeast - Booysen, Clifford (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric.)--University of Stellenbosch, 2001.